Implementation of Contextual Learning Models to Improve Poetry Writing Skills Based on Ecoliteracy at Elementary School - Annisa Afiani; Sani Aryanto; Yosi Gumala (Universitas Teuku Umar, 2022)
Writing is one of the language skills. In learning Indonesian, writing skills are needed, one of which is in learning to write poetry. Writing a poem is one of the skills that must be possessed in learning Indonesian, but there are still many students who lack the ability to write a poem. The main factor causing the low skills of students in writing poetry because the learning model applied is less varied. This study aims to describe the planning, implementation, and results of learning to write poetry based on ecoliteracy in fourth grade students of SDN Karang Anyar 03 by using a contextual learning model. Through the application of contextual learning models, students become more active in participating in learning. By giving students the freedom to learn outside the classroom, students will be more enthusiastic and enthusiastic in learning, especially when writing a poem. It also provides meaningful learning for students, especially related to ecoliteracy that is close to students' real lives. The type of research used is Classroom Action Research using the Kemmis and McTaggart models, the stages of research carried out are planning, implementation, action and observation, and reflection. This research was conducted in 2 cycles. Each cycle consists of 3 meetings. The research subjects were fourth grade students at SDN Karang Anyar 03 with a total of 24 students. Data collection techniques used are tests, interviews, observations, and documentation studies. The data analysis technique uses a combined design or qualitatively and quantitatively. The results of the research that have been carried out show that the contextual learning model can improve the poetry writing skills based on ecoliteracy in fourth grade students. This is indicated by the increase in the class average value in the Pre-cycle, Cycle I, and Cycle II. In the pre-cycle, the class average value was 62.3, then it increased in the first cycle to 64.5 and increased again in the second cycle by 76.0. In cycle II, classical completeness was in the very high category because 87% of students scored above the KKM.